Presuppositions of human communications - "Gandhi, Ramchandra" (Delhi, 1974)
All living beings communicate with one another. We have only limited knowledge of the way in which other beings communicate with each other. We know that human beings communicate with one another not only through ideas and gestures, but also through feelings and emotions. In fact, what cannot be communicated through thoughts and gestures can be effectively shared with others through feelings and emotions. At the human level, communication, most of the time, takes place through language. It is well known that language as the medium of communication finds expression through words, both spoken and written. Communication implies a dialogue between people rather than a monologue. But communication always involves certain presuppositions. At least we can mention two important presuppositions: (a) participation of both the speaker and the hearer, or the writer and the reader; and (b) rational consensus. Language is a boon to human society because through it we try not only to communicate, but also to understand the other. In recent centuries, communicative understanding is the sine qua non of important agenda for philosophers, sociologists, critical thinkers and linguists. For example, it has been pointed out by Habermas that communicative understanding is important in the context of critical theory. In order to explain its importance, he talks about the presuppositions of communication.
Keywords: Sociology